حقوق العمال في قانون العمل التايلندي : دراسة تحليلية تكاملية في ضوء الفقه الإسلامي - تؤعالم، عبد الصمد إبراهيم عثمان (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2013)
This study examines workers' rights in Islamic jurisprudence in comparison to the labor law of Thailand. Islamic law honors work and workers and considers working as an act of worship. In Islamic jurisprudence which applies to labor provisions, Islamic law provides for persons employed by a private or joint company. The study shows those provisions with regard to the rights of women and children. This study addresses Thai labor law and articles of Islamic jurisprudence that conform and disagree with these provisions. The conditions of workers in man-made doctrines such as Feudalism, Capitalism and Communism or Socialism respectively demonstrate the failure or these doctrines in their ideology and mechanism in addressing this issue. Meanwhile, Islamic law takes a middle stand between excessiveness and inadequateness and is characterized by justice and moderation as the law of divine origin. The study produces many findings such as permissibility of women to work in accordance with their nature like most women in southern Thailand. The phenomenon of child labor in Thailand demands extensive examination where a number of Thai laws comply with Islamic law. This is based on the protection of their due rights, and recommended kindness and compassion in dealing with them and not to overburden them with work. The Thai labor law does not mention the time to perform the obligatory prayers but it depends on the workers' situation. Thai labor law does not address Friday prayer (salat al-Jumucah), as well as the rights of workers in performing pilgrimage (al-Hajj). It is equally silent about the duration for performing pilgrimage (al-Hajj), while the pension is religiously permissible according to the Islamic Shari cah. Thai law does not address it while stating the service bonus at the end only. The compensation for the damages is legal and stipulated in the law of Thailand. The researcher prevails the permissibility of strike under conditions, and Thai labor law has already provided that.